Students’ Grammatical Errors Made in Speaking English At English Department in UINSU - Ratna Sari Dewi; Yenni Hasnah (English Teaching and Linguistics Journal (ETLiJ), 2022)
The awareness of using standardized structures and rule in using English  especially in speaking is very important for the students who learn English as a second language besides their mother tongue. This study is aimed to find out the types of students’ grammatical errors in speaking English in English Department in UINSU. Qualitative method used in this research. The source of the data  is the documentation from recorded file of interview foreigners from the students who studied in English Department in UINSU. The total number of students is ten students. Then, this data collected and analyzed based on the theory of Two Dulay (1982). From he data collection, it was found that there are five types of grammatical errors in their speaking such as omission, misformation, misordering, over-regulation, and addition. The highest percentage for these errors was addition 29.5 % followed by misformation 25 %, omission 18.1 %, over-generalization 15.9 % .respectively and the lowest one was misordering 11.3 % .To be the causes of these errors were intralingual and interlingual factors.